The role of multiple courtyards in the promotion of convective cooling - Ernest, Raha (2011)
This study is set out to confirm the phenomenon commented on by Hassan Fathy (1986) that the temperature difference between courtyards has a role in the promotion of convective cooling through transitional spaces in a multiple-courtyards building in semi and regions. The transitional spaces situated between courtyards are identified with specific titles such as Takhtabüsh in the Egypt; and Tablinum in a Roman Domus. However, despite the historic significance of these spaces, most studies have mainly focused on the climatic performance of buildings with a single courtyard. Empirical and numerical study has not been conducted on the nature of this phenomenon. In order to confirm this conjecture, this thesis is set out to conduct fieldwork and theoretical investigation.